2009
DOI: 10.1007/s00586-009-1079-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pulsed jet lavage in vertebroplasty on injection forces of PMMA bone cement: an animal study

Abstract: Percutaneous vertebroplasty, comprising of the injection of polymethylmethacrylate (PMMA) into vertebral bodies, is an efficient procedure to stabilize osteoporotic compression fractures as well as other weakening lesions. Besides fat embolism, cement leakage is considered to be one of the major and most severe complications during percutaneous vertebroplasty. The viscosity of the PMMA during injection plays a key role in this context. It was shown in vitro that the best way to lower the risk of cement leakage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 27 publications
5
19
0
Order By: Relevance
“…The same effect of injection pressure reduction could be shown as a side investigation of this study [18].…”
Section: Cement Injectionsupporting
confidence: 76%
“…The same effect of injection pressure reduction could be shown as a side investigation of this study [18].…”
Section: Cement Injectionsupporting
confidence: 76%
“…However, PVP technique is much more prone to adverse cement leaks than kyphoplasty, because the PMMA is injected in a liquid state in case of PVP and the cement would flow through bone path of least resistance [3]. The popularity of the procedure is increasing and used more frequently [7].…”
Section: Introductionmentioning
confidence: 99%
“…The study showed a reduction of injection forces that allows the use of more viscous PMMA cement. This lowers potentially the risk of cement leakage and fat embolization and makes vertebral augmentation safer [29]. It could be shown in a sheep model that lavage of the bone marrow prior to VP prevents cardiovascular complications, reduces injection forces and allows a better control of cement distribution pattern with less leakage [30,31].…”
Section: Introductionmentioning
confidence: 98%
“…This leads theoretically to a reduction of fat embolism by reducing the intravertebral resistance and injection forces [28]. In a cadaveric feasibility study Benneker et al tested the lavage technique in 24 intact vertebral bodies harvested from five osteopenic or osteoporotic human cadaver spines [29]. The study showed a reduction of injection forces that allows the use of more viscous PMMA cement.…”
Section: Introductionmentioning
confidence: 99%